Turismo accesible para personas con discapacidad física, caso de estudio parroquia Casacay. - Quinde Sumba, Jonnathan Fabricio; Delgado Medina, Maylen Xiomara (Machala : Universidad Técnica de Machala, 2024)
This research work consisted of diagnosing the tourist attractions of the Casacay parish, with the purpose of generating strategies on accessible tourism to the attractions of Balneario La Cocha and Laguna Azul. These attractions are of great interest to visitors, providing them with leisure and adventure activities; but at the same time, they present weaknesses and obstacles for the development of accessible tourism since they do not have ramps or barriers for people with physical disabilities. For this reason, we seek to develop a proposal that addresses inclusive strategies for people with physical disabilities so that they can coexist with the outside world without discrimination and inconveniences. According to the structured planning of the research, the descriptive exploratory method was used since it allows a direct approach to the tourist attractions. In addition, an infinite sampling was carried out to obtain the results; instruments such as surveys were applied, which are direct questionnaires to people with physical disabilities, an interview with María Alvarado and observation cards in the attractions of Balneario La Cocha and Laguna Azul. Finally, the proposal was executed with strategies to improve accessibility for people with physical disabilities in which the proposal is intended to implement ramps, maneuvering spaces, surfaces, toilets and signage, as well as the implementation of recreational activities excursion with wheelchairs, adapted kayak, adapted hydrotherapy, trained personnel and amphibious products.
Este trabajo de investigación consistió en diagnosticar los atractivos turísticos que tiene la parroquia Casacay, con el propósito de generar estrategias sobre turismo accesible hacia los atractivos Balneario La Cocha y Laguna Azul. Estos atractivos son de mucho interés para quienes visitan el lugar, brindándoles actividades de ocio y aventura; pero al mismo tiempo presenta debilidades y obstáculos para el desarrollo de turismo accesible ya que no cuenta con las condiciones de adecuadas para personas con discapacidad física. Por esta razón, se busca realizar una propuesta que aborde estrategias inclusivas para las personas que presentan discapacidad física y puedan convivir con el mundo exterior sin discriminación e inconvenientes. De acuerdo a la planificación estructurada de la investigación se empleó el método exploratorio descriptivo ya que permite el enfoque directo con los atractivos turísticos. Además, se realizó un muestreo infinito para obtener los resultados; se aplicó instrumentos como encuestas que son cuestionarios directos a personas con discapacidad física, entrevista dirigida a la Lcda. María Alvarado y fichas de observación en los atractivos Balneario La Cocha y Laguna Azul. Finalmente se ejecutó la propuesta con estrategias para mejorar la accesibilidad a personas con discapacidad física en la cual se pretende la propuesta de implementar rampas, espacios de maniobra, superficies, baterías sanitarias y señalización, así como la realización de actividades recreativas excursión con silla de ruedas, kayac adaptado, hidroterapia adaptada, personal capacitado y productos anfibios.
Keywords: TURISMO ACCESIBLE; DISCAPACIDAD FISICA; ACCESIBILIDAD; ESTRATEGIAS